Biocompatible Polymer Nano-Constructs: A Potent Platform for Cancer Theranostics - Himani Kalita PhD; Manoj Patowary PhD (Technology in Cancer Research & Treatment, 2023)
Nano-constructs of biocompatible polymers have drawn wide attention owing to their potential as theranostics for simultaneous therapy and detection of cancer. The present mini review summarizes various nano-architectures of polymers that have been developed as theranostic agents for the simultaneous treatment and diagnosis of cancer in a single platform. Additionally, research prospects of polymeric cancer theranostics for the future have been highlighted.